Lateralization of Eye Use in Cuttlefish: Opposite Direction for Anti-Predatory and Predatory Behaviors - Schnell, Alexandra K.; Hanlon, Roger T.; Benkada, Aïcha; Jozet-Alves, Christelle (Frontiers in Physiology, 2016)
Vertebrates with laterally placed eyes typically exhibit preferential eye use for ecological activities such as scanning for predators or prey. Processing visual information predominately through the left or right visual field has been associated with specialized function of the left and right brain. Lateralized vertebrates often share a general pattern of lateralized brain function at the population level, whereby the left hemisphere controls routine behaviors and the right hemisphere controls emergency responses. Recent studies have shown evidence of preferential eye use in some invertebrates, but whether the visual fields are predominately associated with specific ecological activities remains untested. We used the European common cuttlefish, Sepia officinalis, to investigate whether the visual field they use is the same, or different, during anti-predatory and predatory behavior. To test for lateralization of anti-predatory behavior, individual cuttlefish were placed in a new environment with opaque walls, thereby obliging them to choose which eye to orient away from the opaque wall to scan for potential predators (i.e. vigilant scanning). To test for lateralization of predatory behavior, individual cuttlefish were placed in the apex of an isosceles triangular arena and presented with two shrimp in opposite vertexes, thus requiring the cuttlefish to choose between attacking a prey item to the left or to the right of them. Cuttlefish were significantly more likely to favor the left visual field to scan for potential predators and the right visual field for prey attack. Moreover, individual cuttlefish that were leftward directed for vigilant scanning were predominately rightward directed for prey attack. Lateralized individuals also showed faster decision-making when presented with prey simultaneously. Cuttlefish appear to have opposite directions of lateralization for anti-predatory and predatory behavior, suggesting that there is functional specialization of each optic lobe (i.e. brain structures implicated in visual processing). These results are discussed in relation to the role of lateralized brain function and the evolution of population level lateralization.